Kajian kes ke atas kesan kaedah pembelajaran koperatif teknik ’Jigsaw’ dalam kursus isyarat dan sistem - Hafizah Husain; Dzuraidah Abdul Wahab; Aini Hussain; Salina Abdul Samad; Azah Mohamed; Che Husna Azhari; Nooritawati Md. Tahir (Penerbit Universiti Kebangsaan Malaysia, 2010)
The student oriented cooperative leaning method (COOP) exhibit an active teaching methodology in small groups, as compared to the lecturer oriented competitive learning method (COMP). The Jigsaw technique is a subset of the COOP learning that has been demonstrated to nurture good group interaction skill, critical thinking ability, and positive attitude among students that are in agreement with the current outcome based paradigm. In this study, both methods were used in the revision process to reinforce the understanding of the topics taught in the class. This paper specifically discusses both methodologies that have been implemented in Signal and System course (KL2093) at the 13 Engineering Faculty, UKM and analyzes its quantitative and qualitative effectiveness. It also compares the cooperative and competitive structure using the quasi-experiment design approach. The quantitative analysis was carried out on two data sets of examination scores to evaluate their effects towards academic achievements, while, the qualitative analysis based on cause-effect process is performed to investigate the effects towards students’ behavior. Preliminary observation and analysis indicates that the student oriented jigsaw technique is more effective compared to the traditional lecturer oriented COMP learning